DEVELOPED SPECTOPHOTOMETRIC DETERMINATION OFSALBUTAMOL SULPHATE IN PHARMACEUTICAL SAMPLES BYCOUPLING WITH O-NITROANILINE - Hadi, Hind (Iraqi Journal of Science, 2024)
A simple, rapid and sensitive spectrophotmetic method for trace determination of salbutamol sulphate (SBS) in aqueous solution and in pharmaceutical preparations is described .The method is based on the coupling reaction of the intended compound with diazotized o-nitroaniline (DONA) in alkaline medium to form an intense yellow-orange, water soluble dye that is stable and shows maximum absorption at 448 nm .A working curve of absorbance versus concentration indicates that Beer’s low is obeyed over the concentration range of 50-1000 g of SBS in a final volume of 25-ml ( i.e. 2-40 ppm), with a molar absorpativity of 1.58×104 L.mol-1.cm-1 ,a sandell’s sensitivity of 0.0365 g.cm-2 ,a relative error of (-1.156) – 2.874  and a relative standard deviation of 0.735-1.992  depending on the concentration of SBS. The optimum conditions and stability of the colored product have been investigated and the method was applied successfully to the determination of SBS in dosage forms.